2020
DOI: 10.3389/fmicb.2020.536865
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing System Affects the Plant Growth Promotion Traits of Serratia fonticola GS2

Abstract: Quorum sensing (QS) enables bacteria to organize gene expression programs, thereby coordinating collective behaviors. It involves the production, release, and population-wide detection of extracellular signaling molecules. The cellular processes regulated by QS in bacteria are diverse and may be used in mutualistic coordination or in response to changing environmental conditions. Here, we focused on the influence of the QS-dependent genes of our model bacterial strain Serratia fonticola … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Recent studies have indicated that genes involved in plant growth -promoting effects, bio lm formation, plant colonization, and in triggering induced systemic resistance are regulated by QS systems (Jung et al 2017;Zuniga et al 2017). Our results showed that genome of B19 possessed lsr B,C,D,F genes involved in internalizing, phosphorylating and processing of the AI-2, a small signaling molecule in quorum-sensing (QS) (Torres Cerna et al 2019).…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies have indicated that genes involved in plant growth -promoting effects, bio lm formation, plant colonization, and in triggering induced systemic resistance are regulated by QS systems (Jung et al 2017;Zuniga et al 2017). Our results showed that genome of B19 possessed lsr B,C,D,F genes involved in internalizing, phosphorylating and processing of the AI-2, a small signaling molecule in quorum-sensing (QS) (Torres Cerna et al 2019).…”
Section: Discussionmentioning
confidence: 61%
“…A study done by Von Rad and colleagues [54] showed that treatment with oxo-C6-homoserine lactone provided the expression of genes associated with the auxin and cytokinin pathways. Moreover, a study conducted by Jung et al [55] suggested that plant growth promotion affected the plant growth promotion trait of Serratia fonticola GS2, a quorum-sensing bacterial strain through transcriptome observation. In this study, the treated samples generally showed better growth in terms of the parameters used.…”
Section: Discussionmentioning
confidence: 99%
“…have been carried out on plants cultivated under different cultivation conditions. For instance, after inoculation of rice plants with S. glossinae GS2 and S. fonticola GS2, studies conducted in a climate chamber showed a significant increase in plant growth parameters and chlorophyll content ( Jung et al, 2017b , 2020 ). Interestingly, Jung et al (2017a , b) , by liquid chromatography, also showed that the rhizospheric strains S. glossinae GS2 and S. fonticola GS2 are capable of producing quorum-sensing (QS) signaling molecules (N-hexanoyl-L-homoserine lactone and N-octanoyl-L-homoserine lactone) that play an important role in biofilm formation and plant-microbe interactions.…”
Section: Serratia Spp Strains As Plant Growth-promoting Bact...mentioning
confidence: 99%